Frequency-enhanced triboelectric-electromagnetic hybrid generator integrated with multi-generation units for wind energy harvesting. Issue 1 (1st January 2023) - Ye, Hui; Sha, Shujing
Abstract: For a sustainable energy harvesting method, triboelectric nanogenerator (TENG) is becoming more and more important in natural wind energy harvesting. However, harvesting capacity of the TENG is affected by the low frequency of natural wind. To effectively harvest wind energy, a frequency-enhanced triboelectric-electromagnetic hybrid generator (FE-TEHG) is proposed, which integrates generation units. It contains a cam structure with six noses to increase the frequency of the wind. And in the generation units, the TENG module is integrated into the follower, and the electromagnetic generator (EMG) module is integrated into the driving part. Experiments proved that by increasing the input frequency, the output electrical signal of the TENG module becomes six times the original, and this integration method can greatly improve the output capacity of the generator. In the process of charging a 100 μF capacitor to 1.50 V, the charging speed of the FE-TEHG is 1.58 times that of the TENG module. In addition, when the wind speed is about 9 m/s, the FE-TEHG can light up 640 light-emitting diodes (LEDs) and supply power for a thermometer normally. Therefore, this paper provides a valuable method for frequency enhancement and integrated design of the TENG in wind energy harvesting.